Observasi Kelas Sebagai Salah Satu Teknik Supervisi Pengajaran Oleh Kepala Sekolah - Martinus M.Krowin (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2016)
Many ways that can be taken in the supervision of the teaching is done by the supervisor. One way is with classroom observation. Through classroom observations will help assess and improve the factors that affect the learning process of learners. In addition to co-ordinate, stimulate and lead to the growth of the teaching profession. Thus, the supervision is done by the supervisor is really a relief, guidance and coaching appropriate and effective.